Growing the portfolio: circular economy through water reuse in Iran - Al-Saidi, Mohammad; Dehnavi, Sudeh (Frontiers in Water, 2024)
In Iran, water scarcity is increasing due to the rapid growth in economy and population, but also due to waste and overuse. Marginal water resources (unutilized water of lower quality) can provide important options to augment water supply or replace freshwater use. In this way, they can reconcile the seemingly opposing views of water development and water management. Encouraging reuse and circulation of marginal water can enhance water availability and conserve freshwater. This paper analyses water reuse options and policies in Iran. It explains policy constraints based on the type of water for reuse and compares the water reuse policies in Iran to regional experiences. Such a contextualization of Iran’s policies from a regional perspective provides opportunities for mutual learning and lessons for policy reforms. For Iran, there is a need for investments and comprehensive reuse policies. New water sources need to be appropriately identified, treated, delivered and accepted by end-users and society.